2008
DOI: 10.1364/oe.16.011836
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of the 1.4 μm emission of Tm^3+ ions in TeO_2-WO_3-PbO glasses

Abstract: In this work, we report the spectroscopic properties of the infrared 3H4-->3F4 emission of Tm3+ ions in two different compositions of glasses based on TeO2, WO3, and PbO for three Tm2O3 concentrations (0.1,0.5, and 1 wt%). Judd-Ofelt intensity parameters have been determined and used to calculate the radiative transition probabilities and radiative lifetimes. The infrared emission at around 1490 nm corresponding to the 3H4-->F4 transition has two noticeable features if compared to fluoride glasses used for S-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 32 publications
2
24
2
1
Order By: Relevance
“…2. The band positions in this spectrum are similar to those reported in earlier papers [1,2,4,5,16] except minor variations in their relative positions, broadening and intensities due to changes of chemical environment around the Tm 3+ ion. The observed energy levels obtained from the absorption spectra have been analyzed using the free-ion Hamiltonian model as explained in our earlier [24].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…2. The band positions in this spectrum are similar to those reported in earlier papers [1,2,4,5,16] except minor variations in their relative positions, broadening and intensities due to changes of chemical environment around the Tm 3+ ion. The observed energy levels obtained from the absorption spectra have been analyzed using the free-ion Hamiltonian model as explained in our earlier [24].…”
Section: Resultssupporting
confidence: 86%
“…The estimated uncertainties of the JO parameters shown in Table 2 were found to be larger than those estimated for Er 3+ :oxyfluoride glass [34] but smaller than those found for Er 3+ :LiNbO 3 crystal [35]. As can be seen from Table 2, it is observed that the trend of JO parameters (˝2 >˝4 >˝6) is found to be same for phosphate [1], germanate [2], PKBAT [16], fluorophosphate [27], borate [28], tellurite [29], ZBLAN [30], ZBLALi [31], indium-fluoride [31], CaBaMg aluminate [32] and fluoro-indate [33] glasses. The trend of˝2 >˝6 >˝4 is noted for PKMAT similar that of oxyfluoroborate [11] glasses and the trend of˝6 >˝2 >˝4 was observed for tellurite [12] glass.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Compared with the RE 3+ doped LAG phosphors, the RE 3+ -Yb 3+ codoped LAG glasses also show comparable color purities. The high transparency and efficient UC in doped LAG glasses also show great potential applications in visible lasers and 3D displays [30].…”
Section: Resultsmentioning
confidence: 99%
“…In the specific case of optical amplifiers for telecommunication application, it could be concluded that the most adequate properties were observed on the (DESURVIRE et al, 1987;MEARS et al, 1987 VAN DER ENDE et al, 2009;LAHOZ et al, 2011), telas (MACIEL et al, 2000GOUVEIA-NETO et al, 2008;CAO et al, 2012) e marcadores biológicos (VETRONE et al, 2009;BOGDAN et al, 2011;HAASE e SCHÄFER, 2011) (BALDA et al, 2008;SIMPSON, 2008;XIE et al, 2011;LI et al, 2012 PANDOZZI et al, 2005;WATEKAR et al, 2005;SIMPSON et al, 2008;XIE et al, 2011). Na literatura também são reportadas as codopagens de íons Tm 3+ e Er 3+ em matrizes com baixa energia de fônon tais como vidros teluritos, germanatos, oxifluoretos entre outras, a fim de se obter um alargamento de banda (MATTARELLI et al, 2005;TIKHOMIROV et al, 2008;MONTEIRO et al, 2013 (RIGHINI et al, 2002;ZAMPEDRI et al, 2003;ALMEIDA et al, 2004;ALMEIDA et al, 2005 também tem sido reportados na literatura (GONCALVES et al, 2002;GONÇALVES et al, 2004;ZAMPEDRI et al, 2004;BERNESCHI et al, 2011).…”
Section: Introductionunclassified